Transcultural nationalism in Hispano-Filipino literature - Villaescusa-Illán, Irene (Historical and cultural interconnections between Latin America and Asia., 2020)
This book constitutes so far the most compelling and sound research in the area of Philippine literature in Spanish. By exploring identity and nationalism in four Philippine writers in the Spanish language during the American occupation, the author rediscovers a marginalized literary tradition punctuated by political resistance and an uncommon originality." --Jorge Mojarro, University of Santo Tomas, Philippines This book studies a selection of works of Philippine literature written in Spanish during the American occupation of the Philippines (1902-1946). It explores the place of Filipino nationalism in a selection of fiction and non-fiction texts by Spanish-speaking Filipino writers Jesús Balmori, Adelina Gurrea Monasterio, Paz Mendoza Guazón, and Antonio Abad. Taking an interdisciplinary approach that draws from Anthropology, History, Literary Studies, Cultural Analysis and World Literature, this book offers a comparative analysis of the position of these authors toward the cultural transformations that have taken place as a result of the Philippines' triple history of colonization (by Spain, the US, and Japan) while imagining an independent nation. Engaging with an untapped archive, this book is a relevant and timely contribution to the fields of both Filipino and Hispanic literary studies. Irene Villaescusa Illán is a lecturer of literature and cultural analysis at the University of Amsterdam. She is the coeditor of Other Globes: Past and Peripheral Imaginations of Globalization.